Morphological and hand grip strength characteristics and differences between participants of the 2022 world rowing championship - Busta, J.; Hellebrand, J.; Kinkorová, I.; Macas, T. (Frontiers in Sports and Active Living, 2023)
Introduction: Rowing is a strength endurance type of sport, and morphology and mass are undoubtedly performance-related factors. Precisely identifying these morphological factors associated with performance, can assist the exercise scientists and coaches in selecting and developing talented athletes. There is however, a lack of anthropometric data collected at either World Championship or Olympic Games level. The aims of this study were to describe and compare the morphology and basic strength characteristic of male and female heavyweight and lightweight rowers competing at 2022 World Championship (18.-25. September, Racice, Czech Republic).